Low O2 level enhances CH4-derived carbon flow into microbial communities in landfill cover soils. (March 2020) - He, Ruo; Su, Yao; Leewis, Mary-Cathrine; Chu, Yi-Xuan; Wang, Jing; Ma, Ruo-Chan; Wu, Donglei; Zhan, Liang-Tong; Herriott, Ian Charold; Leigh, Mary Beth
Abstract: CH4 oxidation in landfill cover soils plays a significant role in mitigating CH4 release to the atmosphere. Oxygen availability and the presence of co-contaminants are potentially important factors affecting CH4 oxidation rate and the fate of CH4 -derived carbon. In this study, microbial populations that oxidize CH4 and the subsequent conversion of CH4 -derived carbon into CO2, soil organic C and biomass C were investigated in landfill cover soils at two O2 tensions, i.e., O2 concentrations of 21% ("sufficient") and 2.5% ("limited") with and without toluene. CH4 -derived carbon was primarily converted into CO2 and soil organic C in the landfill cover soils, accounting for more than 80% of CH4 oxidized. Under the O2 -sufficient condition, 52.9%–59.6% of CH4 -derived carbon was converted into CO2 (CECO2-C ), and 29.1%–39.3% was converted into soil organic C (CEorganic-C ). A higher CEorganic-C and lower CECO2-C occurred in the O2 -limited environment, relative to the O2 -sufficient condition. With the addition of toluene, the carbon conversion efficiency of CH4 into biomass C and organic C increased slightly, especially in the O2 -limited environment. A more complex microbial network was involved in CH4 assimilation in the O2 -limited environment than under the O2 -sufficient condition. DNA-based stable isotope probing of the community with 13 CH4 revealed that Methylocaldum and Methylosarcina had a higher relative growth rate than other type I methanotrophs in the landfill cover soils, especially at the low O2 concentration, while Methylosinus was more abundant in the treatment with both the high O2 concentration and toluene. These results indicated that O2 -limited environments could prompt more CH4 -derived carbon to be deposited into soils in the form of biomass C and organic C, thereby enhancing the contribution of CH4 -derived carbon to soil community biomass and functionality of landfill cover soils (i.e. reduction of CO2 emission). Graphical abstract: Image 1 Highlights: Methanotrophs secreted more organic-C into the habits in O2 -limited environments. CH4 -derived carbon was primarily converted into CO2 -C and soil organic-C Carbon conversion efficiency of CH4 was higher in O2 -limited environments Microbial network was more complex in O2 -limited environments Toluene could slightly prompt CH4 -derived carbon into biomass C and organic C Abstract : O2-limited environments could prompt more CH4-derived carbon to be assimilated and sequestered in landfill cover soils, thereby reducing greenhouse gas emissions.